Pengaruh Penggunaan Medial Arch Support Terhadap Kelincahan Siswa Ekstrakurikuler Sepak Bola di SMP - Hisyam Syafi’ie; Fendy Wartanto (Jurnal Health Sains, 2022)
Agility is the ability to change the direction of movement quickly and precisely when it is moving without losing balance and awareness of its position, and agility is needed in improving performance in sports, one of which is football, many soccer players feel exhausted so their agility decreases. Decreasing agility can be anticipated using medial arch support. The purpose of this study was to determine the effect of the use of medial arch support on students' skills in football extracurricular activities at SMP Negeri This type of research is Quasy Experiment with a one group pre and post test design design approach. The subjects used were some students of class VII and VIII of SMP N 1 Sambirejo who participated in football extracurricular activities, chosen by using purposive sampling method that met the inclusion and exclusion criteria so that 23 subjects were obtained Using the sampel paired t test hypothesis test where it is known asymp. Sig. (2tailed) worth 0,000, because it is smaller than <0.05, it can be concluded that there is an influence on the use of medial arch support for the flexibility of students in football extracurricular activities at SMP Negeri 1 Sambirejo